2016
DOI: 10.1177/0192512115596368
|View full text |Cite
|
Sign up to set email alerts
|

Electoral systems, ethnic cleavages and experience with democracy

Abstract: Recent studies show that the effects of electoral systems and ethnic cleavages on the number of parties in emerging democracies differ from those effects observed in more established democracies. Building on recent arguments maintaining that the quality of democracy improves with experience, we argue the reason for the differences in the findings between established and emerging democracies is that the effects of these variables on the number of parties differ according to a country’s experience with elections… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Several works have found evidence that over time party leaders learn how to target voters and voters how to avoid wasting their votes, thus leading to more predictability and improved electoral coordination (Crisp et al, 2012;Riera, 2013;Roussias, 2022;Tavits and Annus, 2006). This experience, in turn, should lead to electoral results more in line with conventional theoretical expectations (see Raymond et al, 2016). This hypothesis makes sense.…”
Section: Explaining the Number Of Parties In New Democraciesmentioning
confidence: 74%
See 1 more Smart Citation
“…Several works have found evidence that over time party leaders learn how to target voters and voters how to avoid wasting their votes, thus leading to more predictability and improved electoral coordination (Crisp et al, 2012;Riera, 2013;Roussias, 2022;Tavits and Annus, 2006). This experience, in turn, should lead to electoral results more in line with conventional theoretical expectations (see Raymond et al, 2016). This hypothesis makes sense.…”
Section: Explaining the Number Of Parties In New Democraciesmentioning
confidence: 74%
“…To analyze the impact of electoral experience, we start by segmenting the data between early and late elections. This selection of observations builds on previous work (Raymond et al, 2016;Roussias, 2022), which has shown that it takes about five elections for voters and party leaders to learn how to behave strategically in electoral competition. We thus consider the first five elections after the transition to democracy in every country as early elections, and the rest as late ones.…”
Section: Experience With Democratic Elections Under New Electoral Rulesmentioning
confidence: 96%
“…Tavits and Annus, 2006: 80-87;Maškarinec, 2016). Similarly, Raymond et al (2016) confirmed that the effects of electoral systems and social cleavages significantly differ between emerging and established democracies, but the variability in these effects tends to narrow with more experience with consecutive elections in new democracies (cf. Raymond et al, 2016: 556-562).…”
Section: Introductionmentioning
confidence: 77%
“…Given these information scarcities, voter behaviour is severely hindered in early elections; among other things, new party systems are characterized by extreme volatility (Bielasiak, 2002;Birch, 2003;Kuenzi and Lambright, 2001;Roberts and Wibbels, 1999), high numbers of parties (Filippov et al, 1999;Golder and Wantchekon, 2004) and frequent electoral law changes. However, while scholars have paid attention to this issue (Bernhard and Karakoç, 2011;Crisp et al, 2012;Lago and Martínez i Coma, 2012;Mishler and Rose, 2007;Raymond et al, 2016;Reich, 2004;Riera, 2013;Selb, 2012;Tavits, 2005;Tavits and Annus, 2006), we do not have a clear understanding of the duration and the causes of these characteristics.…”
Section: Department Of Politics and International Relations Universit...mentioning
confidence: 99%